Electronically Verified Use of Internet-Based, Multimedia Decision Aids by Adolescents With Type 1 Diabetes and Their Caregivers. Issue 1 (April 2018) - Wysocki, Tim; James, Lauren; Milkes, Amy; Taylor, Alex; Pierce, Jessica; Brinkman, William B.; Carakushansky, Mauri; Ross, Judith; Hirschfeld, Fiona
Decision aids (DAs) are central to shared decision making (SDM) interventions, yet little is known about patients' actual DA use. Adequate utilization of DAs could optimize SDM effectiveness. Electronic DAs enable more objective tracking and analysis of actual DA utilization than do paper DAs. This report is part of an ongoing randomized controlled SDM trial enrolling adolescents with type 1 diabetes and their caregivers ( n = 153) who were considering use of an insulin pump or continuous glucose monitor. Extensive stakeholder engagement guided creation of two online DAs. After completing baseline measures, 133 dyads were randomized to SDM (access to the pertinent DA) or Usual Care (clinic routines for preparing candidates for adopting these devices). Utilization data showed that 80% of caregivers and 66% of youths logged into a DA at least once; youths and caregivers, respectively, dedicated a mean of 44.7 and 55.0 minutes to website use and viewed 72.2% and 77.4% of the DA content. Median total duration from enrollment to last DA logout was 48.2 days for adolescents and 45.6 days for caregivers. Bivariate comparisons showed that non-Hispanic, Caucasian females from households with higher socioeconomic status were significantly more likely to login to the assigned DA at least once. Hierarchical multiple regression showed that adolescent males with lower levels of health literacy demonstrated fewer DA logins ( F = 2.59; P < 0.009), but identified no significant predictors of adolescents' or caregiver' duration of DA use or proportion of DA content viewed. Future SDM trials should seek to promote DA use, especially by non-White adolescents, perhaps with direct assistance with the initial DA login. Trials employing electronic DAs should routinely report and analyze utilization data.